Implementasi Konsep ESG (Environmental, Social, and Governance) dalam Pengembangan Ekonomi Biru di Kawasan Indo Pasifik: Studi Kasus Chairmanship Indonesia di ASEAN Tahun 2023 - Miftah Febrianti; Aep Saefullah; Nurhayati Nurhayati; Tohhiroh Tohhiroh (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The Indo Pacific region is an area rich in natural resources and has great economic potential. However, rapid economic growth and lack of awareness of environmental protection and social sustainability have led to negative impacts on the environment and society in the region. To overcome this problem, the ESG (Environmental, Social, and Governance) concept has been widely recognized as a framework for encouraging sustainable economic growth by considering environmental, social and good governance factors. The purpose of this research is to examine how the ESG concept is applied in the development and development of the blue economy in the Indo Pacific Region, especially during Indonesia's tenure as chairman of ASEAN in 2023. In this research, we will identify the concrete steps taken by Indonesia in implementing the concept. ESG and promoting the blue economy in the region. This research uses a descriptive qualitative approach method. Data was processed and collected using questionnaires and library literature. The research object consisted of 50 STIE Ganesha student respondents. By analyzing the policies and initiatives launched by the Indonesian government during their leadership in ASEAN. Relevant data will be collected through literature reviews and official documents. It is hoped that the results of this research will provide a better understanding of Indonesia's efforts to implement ESG concepts and promote the blue economy in the Indo Pacific Region. This research limits the scope by using students' perspectives regarding the ESG concept in developing the blue economy in the Indo Pacific region. This research can also provide insight into the challenges faced and the opportunities that exist in developing a sustainable economy in this region. Relevant policy implications will also be identified to support the future development of the blue economy.